Evaluation of thyroid profile in patients with type 2 diabetes mellitus in a tertiary care hospital in Nepal - Yadav, Santosh Kumar; Mallik, Sneha; Khattri, Bishal (Journal of Biomedical Sciences, 2024)
Background: Diabetes mellitus and thyroid disorders are among the two most common endocrine disorders encountered in clinical settings. These two disorders are shown to influence each other, and scholars generally report an association between both conditions. Uncontrolled thyroid disorders can result in abnormal glycemic control in diabetic patients. Thyroid disorder is mainly manifested in patients suffering from diabetes and is associated with increased age, especially in type 2 diabetes. This study aims to establish the prevalence of thyroid disorder in type 2 diabetes mellitus, to estimate fasting blood glucose levels, and to detect glycated haemoglobin (HbA1c) levels in euthyroid, hypothyroid, and hyperthyroid subjects. Material and methods: The present hospital-based cross-sectional study was conducted on 66 subjects aged 21 to 80. The thyroid hormones were evaluated using the ELISA method, and HbA1c was estimated using the High-performance liquid chromatography (HPLC) method. Results: The present study showed the majority of participants were 41-60 years old and had a higher prevalence of hypothyroidism (21.21%) in type 2 diabetes mellitus (T2DM), but the prevalence of hyperthyroidism was lower, 10.60% in T2DM. Conclusion: T2DM was found to be more common among older adult groups (41-60 years). Hypothyroidism was more prevalent compared to hyperthyroidism in diabetes mellitus. Therefore, timely diagnosis should be made to prevent complications of thyroid disorders in diabetic individuals.